SUMBERDAYA IKAN KEMBUNG (Rastrelliger kanagurta Cuvier 1817) DI PERAIRAN SELAT SUNDA YANG DIDARATKAN DI PPP LABUAN, BANTEN (Resources of Indian Mackerel (Rastrelliger kanagurta Cuvier 1817) in Sunda Strait Water that Landed on PPP Labuan, Banten) - Viska Donita Prahadina; Mennofatria Boer; Achmad Fahrudin (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2015)
ABSTRACTIndian mackerel is one of the small pelagic fish that has an important economic value and the dominant fish catches landed in PPP Labuan. The catch of Indian mackerel decreaseyear to year. Therefore Indian mackerel resources, alleged have over-exploited. The aim of this research was to identify a production pattern, fishing ground, fishing season pattern and identify a more appropriate alternative recommendation for the management of Indianmackerel. The results showedthat the production of Indian mackerel had a fluctuated seasonal pattern. The peak fishing season was in April to August while low season (low catches) in December and January. Distribution of Indian mackerel fishing grounds wasin the waters around the Sunda Strait such as RakataIsland, Rakata Kecil Island, Anak RakataIsland, Panaitan Island, Papole Island, Sebesi Island, Sebuku Island, Jongor and Tanjung Lesung. Utilization status of Indian mackerel has already overfished in biology and economics. Some recommendation for managing Indian mackerel resources that were landed in PPP Labuan such as, reduce the fishing effort, increase the mesh size, and improvementmanagement infishing season and fishing ground.Keywords: Indian mackerel, management, PPP Labuan, Sunda Strait-------ABSTRAKIkan kembung merupakan salah satu ikan pelagis kecil yang memiliki nilai ekonomis penting dan merupakan ikan tangkapan dominan yang didaratkan di PPP Labuan. Hasil tangkapan ikan kembung menurun dari tahun ke tahun. Oleh sebab itu diduga ikan kembung telah mengalami eksploitasi berlebih. Tujuan penelitian ini adalah untuk mengetahui pola produksi, daerah tangkapan, pola musim penangkapan, serta mengidentifikasi alternatif pengelolaan yang lebih tepat. Hasil penelitian menunjukkanbahwa pola produksi ikan kembung berfluktuatif. Musim puncak penangkapan ikan berada pada bulan April hingga Agustus, sedangkan musim paceklik berada pada bulan Desember dan Januari. Sebaran wilayah penangkapan berada di sekitar perairan Selat Sunda seperti di P. Rakata, P. Rakata Kecil, P. Anak Rakata, P. Panaitan, P. Papole, P. Sebesi, P. Sebuku, Jongor serta Tanjung Lesung. Pengelolaan ikan kembung dapat dilakukan dengan cara mengurangi upaya penangkapan, memperbesar ukuran mata jaring, pengaturan musim penangkapan dan daerah penangkapan.Kata kunci: ikan kembung, pengelolaan, PPP Labuan, Selat Sunda